Creation and extinction of cells in Bénard Convection - Wierschem, Andreas; Cerisier, P.; Gallet, P.; Velarde, Manuel (Journal of Non-Equilibrium Thermodynamics, 1997)
The creation and extinction of cells in Benard convection has been recorded with an infrared camera, which detects the radiation emitted by the surface of the liquid layer, hence obtaining the time dependent evolution of the surface-temperature distribution.
UnivIS-Import:2015-03-05:Pub.1997.tech.ITC.stmmec.creati